Plastic bronchitis mimicking with foreign body bronchus in pediatric patient – A review - Swain, Santosh Kumar; Bhattacharyya, Biplob; Mohanty, Jatindra Nath (Indian Journal of Child Health, 2019)
Plastic bronchitis (PB) is an extremely rare clinical entity in pediatric age group where an inspissated cast is found in endobronchial airway leading to respiratory distress. It is a large gelatinous or rigid branching airway cast which can lead to life-threatening episodes. The underlying causes for this PB are pulmonary diseases, congenital heart disease (CHD), and a few other conditions. The endobronchial casts are classified into inflammatory and acellular types. Inflammatory casts are most commonly found in primary lung disease, whereas acellular casts are frequently seen in patients with CHD. Removal of this endobronchial cast rapidly improves this condition. Bronchoscopy with bronchial lavage is considered as the gold standard treatment of PB. The patient is managed by rigid bronchoscopy and removal of this cast from bronchus is like foreign body removal from the tracheobronchial tree. Clinicians should have knowledge for correct diagnosis and treatment of PB. This review article discusses about etiopathology, epidemiology, clinical presentations, and diagnosis and treatment of PB among pediatric patients.